Perinatal outcome in pregnancies with nuchal cord: prospective cross-sectional study at tertiary care institute - Dias, Zaneta; Kore, Shailesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The umbilical cord around the neck of fetus at the time of birth is nuchal cord (NC). NC is blamed as a major cause of fetal distress and perinatal mortality. The present study was undertaken to found out the incidence of nuchal cord at delivery and its perinatal outcomes in babies born with NC. Methods: Total 500 low risk women delivered either vaginally or abdominally after 34 completed weeks of gestation were included in the study. Cases with NC at the time of delivery were taken as study group and the cases which did not have NC served as control group. Various obstetric characteristics and perinatal outcome were studied. Results: The frequency of NC found was 35.6% of all the deliveries. Women with age between 21-25 years showed the maximum presence of NC (11.4%) and NC mostly seen between 38-40 weeks of gestation (24.8%). Presence of NC had no statistical significance on the maternal age, parity, period of gestation, mode of delivery, presence of meconium stained amniotic fluid and fetal distress. Prolonged duration of labour was seen in the presence of NC. The presence of NC was directly proportional to the length of cord and umbilical cord coiling. Perinatal outcome of babies in terms of Apgar score and seen as NICU admissions rate were not statistically significant. Tight NC had a poor Apgar score needed more intensive care. Conclusions: NC is a common finding at the time of delivery. The present study suggests that NC is not associated with significant perinatal outcome.